Resilience as a protective factor for well-being and emotional stability in elite-level football players during the first wave of the COVID-19 pandemic - Elholm Madsen, E.; Krustrup, P.; Hvid Larsen, C.; Elbe, A.-M.; Wikman, J. M.; Ivarsson, A.; Lautenbach, F. (Science and Medicine in Football, 2021)
Background: In Denmark, the first COVID-19 pandemic lockdown resulted in a compact season finisher for elite footballers, potentially impacting their mental health.Purpose: This study aimed to investigate the protective role of resilience and the impeding role of trait anxiety on elite footballers` level and variability of well-being and emotional stability. Material and Methods: One hundred and twenty-five male elite-level players (Mage = 25.04 ± 4.82) completed baseline measures on trait anxiety and resilience. Additionally, well-being and positive and negative affect were assessed before games (n = 24) over 62 days. Separate two-level regression analysis using Bayesian statistics was conducted to test potential relationships. Results: Results show a credible positive relationship between the average level of well-being and within-person variability over time as well as the average level in positive affect. This indicates that resilience might be a protector for mental health. In addition, higher levels of trait anxiety (i.e., subscale concentration disruption) were associated with higher levels of negative affect and higher variability over time. This indicates that trait anxiety might facilitate negative affect. No other credible relationships were found. Conclusion: High resilience and low trait anxiety are identified as relevant factors for mental health within elite footballers during COVID-19. Implications for practice are discussed.